2011
DOI: 10.1002/tax.601013
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of Polygonoideae (Polygonaceae): A new tribal classification

Abstract: The subfamily Polygonoideae has a world‐wide distribution and is an important component of many countries’ floras. In this study we present the most comprehensive sampling available to date, including data from three chloroplast genes (matK, ndhF, rbcL) for 82 species in Polygonaceae (54 from Polygonoideae). Based on our results, we propose a new taxonomic classification for Polygonoideae that includes five well‐supported tribes: Calligoneae, Fagopyreae, Persicarieae, Polygoneae, and Rumiceae. Overall, the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
85
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 48 publications
15
85
1
2
Order By: Relevance
“…1) of one nr (ITS) and three cp ( mat K, ndh F and trn L- trn F) markers for the most part show the same results for the evolutionary relationships among and within all genera included when compared to the ML and Maximum Parsimony analyses of other studies (e.g., [1], [22], [23], [51], [52]). Since the evolutionary relationships among clades and the placement of genera within Polygonaceae are congruent across these studies, these results will not be reiterated here and only differences are discussed briefly.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…1) of one nr (ITS) and three cp ( mat K, ndh F and trn L- trn F) markers for the most part show the same results for the evolutionary relationships among and within all genera included when compared to the ML and Maximum Parsimony analyses of other studies (e.g., [1], [22], [23], [51], [52]). Since the evolutionary relationships among clades and the placement of genera within Polygonaceae are congruent across these studies, these results will not be reiterated here and only differences are discussed briefly.…”
Section: Discussionsupporting
confidence: 66%
“…with approximately 1,200 species [1] is morphologically diverse and growth forms include trees, shrubs, vines, lianas and herbs. Polygonaceae are found in a wide range of habitats from the Arctic to the tropics, from montane to lowland regions, and from arid to aquatic situations.…”
Section: Introductionmentioning
confidence: 99%
“…Systematically, Atraphaxis , Calligonum , and Pteropyrum formerly constituted Tribe Atraphaxideae (Dammer ), or subtribe Atraphaxidinae (Jaretzky ; Hong ), and a Tibetan genus, Parapteropyrum (Li ; Bao and Li ), was a subsequent addition to the group. However, this tribe, including these four genera, was shown to be non‐monophyletic in terms of a recent molecular phylogeny (Lamb‐Frye and Kron ; Sanchez and Kron , , ; Tavakkoli et al ; Sanchez et al , ; Sun and Zhang ). As a result, Atraphaxis is now placed in tribe Polygoneae, while Calligonum and Pteropyrum are located in tribe Calligoneae, distant from Atraphaxis (Sanchez et al , 2011b; Tavakkoli et al ; Sun and Zhang ), and Parapteropyrum is included in Fagopyreae (Sanchez et al 2011a, 2011b).…”
Section: Introductionmentioning
confidence: 92%
“…Molecular analyses of both nrDNA ITS and some cpDNA sequences ( trn L-F, mat K, atp B- rbc L, psb A- trn H, psb K- psb L and rbc L) have not resolved relationships amongst species of Calligonum (Sanchez et al 2011, Sun and Zhang 2012, Li et al 2014). Our study showed that Calligonum ebinuricum possesses highly distinct nrITS sequences (Figures 3 & 4); yet the ITS and ETS sequences of the Calligonum mongolicum complex generated a topology with the species of the complex highly intermixed with each other in the tree.…”
Section: Discussionmentioning
confidence: 99%
“…Medusae . The taxonomic relationships of the genus have been tested by the applications of several molecular techniques, such as the RAPD markers (Ren et al 2002) and other chloroplast DNA markers ( trn L-F, mat K, atp B- rbc L, psb A- trn H, psb K- psb l and rbc L) (Tavakkoli et al 2010; Sanchez et al 2011; Abdurahman and Sabirhazi 2012; Sun and Zhang 2012; Li et al 2014), but the markers employed so far have been inefficient for resolving the taxonomic problems in Calligonum . It was expected that reproductive biology and faster-evolving nuclear DNA sequences (Sang 2002; Zimmer and Wen 2012) might shed some light on the taxonomy of the genus.…”
Section: Introductionmentioning
confidence: 99%